Family Policy Issues in Lithuania: an Analysis of Previous Studies - Senkuvienė, Kristina (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]The article analyzes family policy problems in Lithuania through the prism of research carried out by county’s scientists during the period of independence, as well as through statistical analysis. Family policy issues are addressed through three selected analytical „fields“ that significantly reveal the results of family policy: women’s involvement in the labor market, child poverty and gender equality. Different sections of the article analyze how family support measures in the country affect these aspects of family policy and what main issues are confronted while achieving family policy goals. It is concluded that the state can implement the main goals of family policy only by securing a sustainable and steady family policy oriented towards the creation of conditions necessary for the independent functioning of the family.
Keywords: family policy, child wellbeing, gender equality, balancing of work and family life